Polysiloxane, Adhesive and Humidity Sensor
A new polyxiloxane with reversible softening and moisture absorption properties addresses limitations in existing adhesives and humidity sensors, offering high adhesive performance and effective humidity sensing.
Patent Information
- Application Number
- JP2020083502
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-05-11
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2040-05-11
AI Technical Summary
Existing polyxiloxanes do not exhibit reversible softening and moisture absorption properties, limiting their application as adhesives and humidity sensors.
Development of a new polyxiloxane represented by Equation (1) that softens and cures reversibly due to drying and moisture absorption, with specific organic groups, anions, and cations forming ionic pairs, allowing for high adhesive performance and humidity sensing.
The new polyxiloxane demonstrates reversible softening and moisture absorption, providing excellent adhesive properties and humidity sensing capabilities, including water solubility and washability, making it suitable for temporary fixing and humidity detection.
Smart Images

Figure 0007626418000011 
Figure 0007626418000012 
Figure 0007626418000013
Abstract
Description
[Technical field]
[0001] The present invention relates to a polysiloxane, an adhesive, and a humidity sensor. [Background technology]
[0002] Polysiloxanes, in which silicon and oxygen are alternately bonded, are generally colorless, odorless, and water-repellent, and are widely known to take various forms such as oil and rubber depending on the degree of polymerization and substituents. Such polysiloxanes are used as silicones in a variety of industrial fields, from electronics to chemicals, textiles, food, cosmetics, and construction (Non-Patent Document 1). [Prior art documents] [Non-patent literature]
[0003] [Non-Patent Document 1] Masaaki Yamatani, "Silicones: Expanding Application Fields and Technological Trends", September 2011, Chemical Daily Press Summary of the Invention [Problem to be solved by the invention]
[0004] The present inventors have discovered a new polysiloxane that has properties different from those of the general polysiloxanes described above and can reversibly repeat hardening due to drying and softening due to moisture absorption. The present inventors have also found that this polysiloxane is useful as an adhesive and a humidity sensor.
[0005] An object of the present disclosure is to provide a new polysiloxane that can reversibly repeat hardening due to drying and softening due to moisture absorption, as well as an adhesive and a humidity sensor that use this polysiloxane. [Means for solving the problem]
[0006] One aspect of the present disclosure is a polysiloxane represented by the following formula (1): [ka] (In the formula, A is a single bond or a divalent organic group, B is an alkyl group; X is an anion or a cation, and when X is an anion, Y is a cation which forms an ion pair with X, and when X is a cation, Y is an anion which forms an ion pair with X; R is absent, hydrogen, or a substituted or unsubstituted monovalent organic group. Effect of the Invention
[0007] According to the present disclosure, it is possible to provide a new polysiloxane that can reversibly repeat hardening due to drying and softening due to moisture absorption, as well as an adhesive and a humidity sensor that use this polysiloxane. [Brief description of the drawings]
[0008] [Figure 1] 1 is a diagram illustrating a schematic configuration of a humidity sensor according to an embodiment; [Diagram 2] 2(a) and 2(b) are diagrams showing 29Si-NMR spectra of PAPDMOS-b (Comparative Example 1) and PAPDMOS-a (Example 1), respectively. [Diagram 3] Fig. 3(a) is a diagram showing the results of MALDI-TOF-MS measurement of PAPDMOS-b (Comparative Example 1), and Fig. 3(b) is a diagram showing the results of MALDI-TOF-MS measurement of PAPDMOS-a (Example 1). [Figure 4] FIG. 2 shows GPC charts of PAPDMOS-b (Comparative Example 1) and PAPDMOS-a (Example 1). [Diagram 5] FIG. 1 is a diagram showing the results of evaluating the moisture absorption capacity of PAPDMOS-a (Example 1) and PAPDMOS-b (Comparative Example 1) using an electronic balance. [Figure 6]Fig. 6(a) is a diagram showing the weight change of the film obtained by QCM measurement of PAPDMOS-a (Example 1), and Fig. 6(b) is a diagram showing the weight change of the film obtained by QCM measurement of PAPDMOS-b (Comparative Example 1). [Figure 7] FIG. 1 is a diagram showing the results of evaluating the moisture absorption capacity of PAPDMOS-a (Example 1), PAPDMOS-HBr (Example 3), and PADMOS-b (Comparative Example 1) using an electronic balance. [Figure 8] FIG. 1 is a diagram showing an outline of preparation of a test piece for an adhesion test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, embodiments for carrying out the present disclosure will be described in detail with reference to the drawings, etc. The embodiments are illustrative and do not limit the invention, and all of the features and combinations thereof described in the embodiments are not necessarily essential to the invention.
[0010] (definition)
[0011] An "alkyl" group refers to a linear or branched monovalent aliphatic hydrocarbon group. Examples of alkyl groups include, but are not limited to, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, and the like.
[0012] A "heteroalkyl" group means that one or more of the carbon atoms in the backbone of an alkyl group have been replaced with a heteroatom, such as, for example, an oxygen atom (O), a sulfur atom (S), a nitrogen atom (N), a phosphorus atom (P), and the like.
[0013] An "alkoxy" group refers to an -O-alkyl group, where alkyl is as defined above. Examples of alkoxy groups include, but are not limited to, methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, sec-butoxy, tert-butoxy, and the like.
[0014] A "cycloalkyl" group refers to a monocyclic or polycyclic cycloalkyl group. Examples of cycloalkyl groups include, but are not limited to, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, and the like.
[0015] A "heterocycloalkyl" group refers to a cycloalkyl group that contains 1 to 3 heteroatoms selected from N, O, P, or S.
[0016] An "aryl" group refers to a monocyclic or polycyclic aromatic hydrocarbon group. Examples of aryl include, but are not limited to, phenyl, naphthyl, tetrahydronaphthyl, and the like.
[0017] An "arylalkyl" group refers to an aryl group substituted with a lower alkyl, e.g., an alkyl group having 1 to 5 carbon atoms, such as methyl, ethyl, propyl, etc. Examples of aryl groups include, but are not limited to, benzylmethyl, phenylethyl, etc.
[0018] As used herein, an "aryloxy" group refers to an -O-aryl group, where the aryl group is as defined above. Examples of the aryloxy group include a phenoxy group, a naphthoxy group, an anthracenyloxy group, a phenanthrenyloxy group, a fluorenyloxy group, an indenyloxy group, and the like. One or more hydrogen atoms contained in the aryloxy group may be substituted with an alkyl group.
[0019] As used herein, a "heteroaryl" group refers to a mono- or polycyclic aromatic ring compound containing one to three heteroatoms selected from the group consisting of N, O, P and S, with the remaining ring atoms being carbon atoms.
[0020] As used herein, a "heteroarylalkyl" group refers to a heteroaryl group substituted with a lower alkyl group, where the heteroaryl in the heteroarylalkyl group is defined above.
[0021] As used herein, a "heteroaryloxy" group refers to the group --O-heteroaryl, where heteroaryl in the heteroaryloxy group is defined above.
[0022] As used herein, "substituted" means substituted in place of hydrogen with at least one substituent such as halogen (fluorine, chlorine, bromine or iodine), nitro, cyano, alkyl, cycloalkyl, heterocycloalkyl, aryl or heteroaryl, provided that the normal valence of the substituted atom is not exceeded.
[0023] (Polysiloxane) The polysiloxane according to the present embodiment is represented by the above formula (1). Such a polysiloxane hardens when dried and softens when it absorbs moisture. This phenomenon of hardening and softening occurs reversibly. Generally, the thermosetting of a resin is irreversible, and once a resin has been thermoset, it will not soften again. In this respect, the polysiloxane according to the present embodiment has very unique properties. In addition, such a polysiloxane has high adhesive performance when dry.
[0024] In the above formula (1), A is a single bond or a divalent organic group. Examples of the divalent organic group include alkylene, heteroalkylene, alkoxylene, cycloalkylene, heterocycloalkylene, arylene, heteroarylene, arylalkylene, heteroarylalkylene, aryloxylene, and heteroaryloxylene. In the above formula (1), B is an alkyl group. This alkyl group may be substituted or unsubstituted.
[0025] In the above formula (1), X is an anion or a cation, and Y is a cation or an anion that forms an ion pair with X. That is, when X is an anion, Y is a cation that forms an ion pair with X, and when X is a cation, Y is an anion that forms an ion pair with X. Examples of such combinations of X and Y include the following. ·X is an ammonium ion and Y is a halide ion. ·X is a carboxylate ion and Y is an alkali metal ion. ·X is a sulfate ion and Y is an alkali metal ion.
[0026] In formula (1), R is absent, hydrogen, or a substituted or unsubstituted monovalent organic group. Examples of R include a substituted or unsubstituted alkyl group, a substituted or unsubstituted heteroalkyl group, a substituted or unsubstituted alkoxy group, a substituted or unsubstituted cycloalkyl group, a substituted or unsubstituted heterocycloalkyl group, a substituted or unsubstituted aryl group, a substituted or unsubstituted heteroaryl group, a substituted or unsubstituted arylalkyl group, a substituted or unsubstituted heteroarylalkyl group, a substituted or unsubstituted aryloxy group, or a substituted or unsubstituted heteroaryloxy group.
[0027] The polysiloxane of the present embodiment is preferably linear and has no branching. The structure of the polysiloxane can be confirmed by a known method using NMR.
[0028] The polysiloxane of the present embodiment has a storage modulus of 1.8x10 at 0% humidity. 8 Pa~8.1x10 8 Pa, and the storage modulus at 80% humidity is 6.2x10 0 Pa~1.0x10 1 It is preferable that the storage modulus is 1 / 2 or less. Here, the storage modulus refers to a value measured at room temperature using a rheometer. Such a change in the storage modulus of the polysiloxane of the present embodiment occurs reversibly. Furthermore, the polysiloxane of the present embodiment is almost liquid at a humidity of 80%, but has a resin-like hardness at a humidity of 0%, i.e., in a dry state.
[0029] The polysiloxane of the present embodiment preferably has a tensile shear adhesive strength of 0.8 MPa or more in a dry state to an ozone oxidation treated substrate. By having such an adhesive strength in a dry state, the polysiloxane of the present embodiment can function as an adhesive. The method for measuring the tensile shear adhesive strength here is as described in the following examples.
[0030] The polysiloxane of the present embodiment can be produced by using a known hydrosilylation reaction (see, for example, Adv. Synth. Catal. 2002, 344, 1142-1145; J. Mater. Chem., 2012, 22, 7676-7680) and appropriately combining commercially available reagents. An example of a synthesis scheme is shown below. In the scheme, A, B, X, and R are as defined in the above formula (1), and X' is an ionic group corresponding to the cation or anion of X. By treating the polysiloxane obtained after the hydroxylation reaction shown in the scheme with an acid or base, X' can be ionized to form an ion pair of X and Y in formula (1). [ka] Here, L is an alkoxy group or chlorine.
[0031] The polysiloxane of the present embodiment can also be produced by hydrolysis and condensation of a silane coupling agent. An example of a synthesis scheme is shown below. The silane coupling agent may be a commercially available one, or may be one synthesized according to a known method. The reaction conditions for hydrolysis and condensation of the silane coupling agent can be appropriately selected depending on the target substance. [ka] In the scheme, A, B, X, Y, R and L are as defined above.
[0032] (glue) Another embodiment of the present disclosure is an adhesive. This adhesive contains the above-mentioned polysiloxane. Such an adhesive can reversibly repeat hardening by drying and softening by absorbing moisture, and exhibits high adhesive performance when dry. In addition, the adhesive of this embodiment is water-soluble and can be washed away with water. Due to these properties, the adhesive of this embodiment is particularly useful as an adhesive for temporary fixing.
[0033] The adhesive of the present embodiment may contain, as appropriate, known additives such as plasticizers, preservatives, fillers, and surfactants, provided that the properties of the polysiloxane are not impaired.
[0034] (humidity sensor) Yet another embodiment of the present disclosure is a humidity sensor. FIG. 1 is a diagram showing a schematic configuration of a humidity sensor according to the present embodiment. The humidity sensor 10 includes a substrate 12 and a humidity-sensitive film 14 containing the polysiloxane formed on the substrate 12. The thickness of the humidity-sensitive film 14 may be approximately the wavelength of visible light, and can be appropriately set by a person skilled in the art. In addition, JIS Z8120:2001 generally defines the short wavelength limit of the wavelength range of visible light as 360 to 400 nm and the long wavelength limit as 760 to 830 nm. The thickness of the humidity-sensitive film 14 changes depending on the surrounding humidity, and specifically, the higher the humidity, the greater the film thickness. Such a change in film thickness changes the interference color of the humidity-sensitive film 14, making it possible to detect humidity. EXAMPLES
[0035] The present embodiment will be described in more detail below with reference to examples, but these examples do not limit the present disclosure in any way.
[0036] (Reagents and Solvents) 3-Aminopropyldimethoxymethylsilane (APDMOS), tetramethylsilane (TMS), 2,5-dihydroxybenzoic acid (DHB), and sodium trifluoroacetate were purchased from Tokyo Chemical Industry Co., Ltd. Hydrochloric acid, triethylamine, hydrobromic acid, acetic acid, sodium nitrate, potassium acetate, potassium carbonate, potassium iodide, and potassium sulfate were purchased from Kishida Chemical Co., Ltd. Lithium chloride, sodium bromide, and potassium chloride were purchased from Kanto Chemical Co., Ltd. These reagents were used as they were without purification. The solvents methanol, ethanol, dimethyl sulfoxide (DMSO), tetrahydrofuran (THF), acetone, and chloroform were purchased from Kishida Chemical Co., Ltd. These solvents were used as they were without purification. Ultrapure water (resistivity: 18.2 MΩcm) purified from tap water using Millipore Direct-Q3 UV was used as water.
[0037] (Synthesis of Hygroscopic Polysiloxane) Polysiloxane was synthesized under basic and acidic conditions. The sample synthesized under basic conditions was labeled PAPDMOS-b and PAPDMOS-a, respectively, with the initial "b" (from "base") and the initial "a" (from "acid") added to the suffix. The amines in the polysiloxane synthesized under basic conditions were ionized by treating it with acid. The sample ionized with hydrochloric acid was labeled PAPDMOS-HCl, and the sample ionized with hydrobromic acid was labeled PAPDMOS-HBr. In this chapter, the phenomenon of moisture absorption under standard atmospheric pressure is defined as "spontaneous moisture absorption."
[0038] (Comparative Example 1: Synthesis of PAPDMOS-b) Add 1.83g (1.1×10) of APDMOS to the sample bottle. -2 mol), triethylamine 6.86g (6.8 × 10 -2 mol), water 4.58g (2.5×10 -1 The sample bottle was capped and stirred for 5 hours at 70°C using a magnetic stirrer. The solvent was then removed using an evaporator, and the mixture was vacuum dried overnight at 40°C using a bell jar vacuum oven to obtain a transparent viscous liquid. The yield was 1.50 g. The product was identified using proton nuclear magnetic resonance spectroscopy ( 1 H-NMR measurements were performed using a JEOL NMR A-400. Measurements were performed using heavy water (D2O) and heavy water with a small amount of sodium deuteroxide added (D2O+NaOD, NaOD concentration: 40wt%) as the measurement solvent. A measurement sample containing sodium deuteroxide was prepared by mixing 10.6mg of sample, 692.6mg of D2O, and 41.0mg of D2O+NaOD. 1 H-NMR(δ[ppm],400MHz,D2O): 0.11(3H,SiCH3), 0.59(2H,SiCH2CH2CH2NH2), 1.60(2H,SiCH2CH2CH2NH2), 2.75(2H,SiCH2CH2CH2NH2), 2.96(2H,SiCH2CH2CH2NH3 + ). 1 H-NMR(δ[ppm],400MHz,NaOD in D2O):-0.18(3H,SiCH3), 0.30(2H,SiCH2CH2CH2CH2NH2), 1.34(2H,SiCH2CH2CH2CH2NH2), 2.43(2H,SiCH2CH2CH2NH2).
[0039] (Example 1: Synthesis of PAPDMOS-a) 2.0g (1.2×10-2mol) of APDMOS and 3.54g (3.6×10-2mol) of concentrated hydrochloric acid were weighed into a sample bottle, the bottle was capped, and the mixture was stirred at room temperature for 2 hours using a magnetic stirrer. The cap was then opened, the heater temperature was set to 60-70°C, and stirring was continued until the solvent was completely removed. The dried sample was dissolved in the minimum amount of methanol, and the magnetic stirrer was removed. After removing the solvent using an evaporator, the mixture was vacuum dried overnight at 40°C using a bell jar type vacuum oven, yielding a translucent solid. The yield was 1.89g. The product was identified using proton nuclear magnetic resonance spectroscopy ( 1 The measurement was performed using an NMR A-400 (JEOL WinAlpha) with deuterated DMSO as the measurement solvent. 1 H-NMR(δ[ppm],400MHz,DMSO-d6):0.00(3H,SiCH3),0.48(2H,SiCH2CH2CH2NH3 + Cl - ), 1.57(2H,SiCH2CH2CH2NH3 + Cl - ), 2.69(2H,SiCH2CH2CH2NH3 + Cl - ), 8.16(3H,SiCH2CH2CH2NH3 + Cl - ).
[0040] Example 2: Synthesis of PAPDMOS-HCl PAPDMOS-b was treated with hydrochloric acid to synthesize PAPDMOS-HCl, in which hydrochloride was added to the amine. First, concentrated hydrochloric acid in an amount of 3 equivalents of monomer was added to PAPDMOS-b of Comparative Example 1, and the sample bottle was capped and stirred with a magnetic stirrer at room temperature for 2 hours. The cap was then opened, the heater temperature was set to 60 to 70°C, and stirring was continued until the solvent was gone. The dried sample was dissolved in the minimum amount of methanol required, and the magnetic stirrer was collected. After removing the solvent with an evaporator, the sample was vacuum-dried overnight in a bell jar type vacuum oven to obtain a translucent solid. 1 H-NMR(δ[ppm],400MHz,DMSO-d6):0.00(3H,SiCH3),0.48(2H,SiCH2CH2CH2NH3 + Cl - ), 1.57(2H,SiCH2CH2CH2NH3 + Cl - ), 2.69(2H,SiCH2CH2CH2NH3 + Cl - ), 8.16(3H,SiCH2CH2CH2NH3 + Cl - ).
[0041] Example 3: Synthesis of PAPDMOS-HBr PAPDMOS-b was treated with hydrobromic acid to synthesize PAPDMOS-HBr, in which the amine was converted to amine hydrobromide. First, 3 equivalents of hydrobromic acid per monomer were added to PAPDMOS-b, and the sample bottle was capped and stirred with a magnetic stirrer at room temperature for 2 hours. The lid was then opened, the heater temperature was set to 60-70°C, and stirring was continued until the solvent was gone. The dried sample was dissolved in the minimum amount of methanol required, and the magnetic stirrer was collected. After removing the solvent with an evaporator, the sample was vacuum-dried overnight in a bell jar-type vacuum oven, resulting in a light brownish translucent solid. 1 H-NMR(δ[ppm],400MHz,DMSO-d6):0.00(3H,SiCH3),0.48(2H,SiCH2CH2CH2NH3 + Cl -), 1.56(2H,SiCH2CH2CH2NH3 + Br - ), 2.74(2H,SiCH2CH2CH2NH3 + Br - ), 7.88(3H,SiCH2CH2CH2NH3 + Br - ).
[0042] ( 29 Si NMR measurement) 29 The SiNMR measurement equipment used was a 500MHz Ultra Shield (Bruker), and deuterated methanol was used as the measurement solvent. As no peak was detected at the TMS concentration (0.03 vol%) in the commercially available deuterated solvent, approximately 10 mg of TMS was added to the deuterated solvent. The concentration of the measurement sample was 10 wt%, and tris(2,4-pentanedionato)chromium(III) was added as a relaxation agent to make it approximately 30 mM. During the measurement, the number of accumulations was set to 128, and the relaxation time was set to 10 seconds.
[0043] (Gel permeation chromatography (GPC) measurement) The pump used was a Chromaster 5110 (HITACHI), the refractive index detector was a Chromaster 5450 (HITACHI), the thermostatic bath was a Chromaster Organizer (HITACHI), and the column oven was a CTO-20A (Shimadzu Corporation). The columns used were SB-804HQ (Shodex) and SB-803HQ (Shodex) connected in series in this order. The eluent was a mixed solvent (25:75 v / v) of methanol and an aqueous solution in which acetic acid and sodium nitrate were each dissolved at a concentration of 0.5 M. The flow rate was 0.75 ml / min, and the column oven temperature was set to 30°C. A calibration curve was prepared using polyethylene glycol for calibration (GL Sciences, molecular weight 400, 1000, 4000, 10000, 100000).
[0044] (Matrix-assisted laser desorption / ionization time-of-flight mass spectrometry (MALDI-TOFMS) measurement) The measurement equipment used was autoflex maX (Bruker). The target plate was MTP Anchor Chip TM384BC (Bruker), and the target frame was MTP target frameIII (Bruker). Sample preparation was performed as follows. First, a methanol solution of 10 mg / ml of polymer sample, 10 mg / ml of matrix (DHB), and 1.2 mg / ml of cationizing agent (sodium trifluoroacetate) was prepared by thoroughly distilling off the solvent. 30 μl of each of these three solutions was measured into a microtube and mixed with a vortex mixer. The weight ratio of the solutes in the solution was polymer sample: matrix: cationizing agent = 25:25:3. A drop of the mixed solution was dropped onto the target plate and dried in a vacuum oven at 40 ° C for 2 hours to completely remove the solvent. The obtained sample was irradiated with a laser and measured. The number of integration times was 10 times during the measurement. The laser was set to about 90 to 100% of its maximum output.
[0045] (Evaluation of thermal hardening by palpation) Approximately 10 mg of a polymer sample that had naturally absorbed moisture was placed on a Teflon (registered trademark) sheet and heated in air at 100° C. for 3 hours. The degree of hardening was evaluated by palpation of the sample with a toothpick before and after heating.
[0046] (In-situ QCM measurements under humidity control) A methanol solution consisting of 2 wt% of the polymer sample was prepared by thoroughly distilling off the solvent. This methanol solution was applied to a QCM substrate (Tama Device, 5 MHz) that had been ozone-cleaned by irradiating vacuum ultraviolet light (VUV) and rotated at 2000 rpm for 30 seconds to obtain a film sample. Before the QCM measurement, the film on the outside of the electrode was wiped off with a cotton swab moistened with methanol. The QCM substrate was attached to a measuring device (Tama Device, THQ-100P-SW type), sealed with a dedicated flow cell (Tama Device), and placed in a cool incubator. The temperature inside the chamber was set to 25°C. The humidity was controlled by supplying nitrogen and water vapor from BEL Flow (MicrotracBEL) into the flow cell at an arbitrary ratio, and the relative humidity was changed from 0% to 90% in 10% increments. The temperature inside the cell was controlled by the temperature of the supplied air and was set to 25°C.
[0047] (Moisture absorption measurement on bulk samples using saturated salt) A Teflon (registered trademark) sheet was placed in a weighing bottle with a lid, and the tared bag was weighed. After that, about 50 mg of a polymer sample that had naturally absorbed moisture was placed on the Teflon (registered trademark) sheet, and vacuum drying was performed for 24 hours in a bell jar type vacuum oven. The weighing bottle was weighed on an electronic balance, and the weight of the polymer sample when dried was calculated from the weight difference with the tared bag. After that, the lid of the weighing bottle was opened and placed in a Ziploc (registered trademark). The lid of the weighing bottle and the saturated salt solution were also placed in the Ziploc and sealed. The humidity inside the Ziploc was controlled between 14% and 97% by using various saturated salt solutions, and the value of the humidity sensor RTR-503 (T&D) placed in the Ziploc was taken as the humidity inside the Ziploc. After 24 hours had passed since sealing, the weighing bottle was covered in the Ziploc, the weighing bottle was removed, and the weight of the weighing bottle was quickly measured on an electronic balance. This operation was repeated to measure the moisture absorption amount at various humidities. Lithium chloride, potassium acetate, potassium carbonate, sodium bromide, potassium iodide, sodium chloride, potassium chloride, and potassium sulfate were used as solutes in the saturated aqueous solution (Japanese Industrial Standards, Hygrometer - Test Method, JIS B7920). The moisture absorption rate of the sample was calculated using the following formula.
number
[0048] (Evaluation of PAPDMOS-b and PAPDMOS-a) PAPDMOS-b and PAPDMOS-a 29 The Si-NMR spectra are shown in Figure 2(a) and Figure 2(b), respectively. Since no peak was observed near -70 ppm due to Si in the T environment, it was determined that the main chains of PAPDMOS-b and PAPDMOS-a are not branched (they do not have a three-dimensional network structure).
[0049] The results of the solubility tests for PAPDMOS-b and PAPDMOS-a are shown in Table 1. PAPDMOS-b was found to be well soluble in water and methanol, and to be water-soluble. PAPDMOS-a was well soluble in water and methanol, and, like PAPDMOS-b, was water-soluble. Unlike PAPDMOS-b, it was also soluble in DMSO, an aprotic polar solvent. [Table 1]
[0050] Next, the results of MALDI-TOF-MS measurements of PAPDMOS-b and PAPDMOS-a are shown in Figures 3(a) and 3(b), respectively. For both samples, a wide spectrum was observed, with a peak top at a molecular weight of about 2000 to 3000, including polymers with molecular weights in the hundreds to tens of thousands. It was found that there was no significant difference in molecular weight depending on the synthesis method. The broad distribution of the amounts is thought to be due to the fact that the polymers were synthesized by hydrolysis polycondensation. In addition, the interval between the observed main peaks was in good agreement with the interval between the monomer units (117.22 m / z), and this result also confirmed that the target samples had been synthesized.
[0051] Next, the GPC chart and analysis results are shown in Figure 4 and Table 2, respectively. Two peaks were observed in both samples. These are thought to be derived from linear and cyclic polymers, respectively. PAPDMOS-b had a number average molecular weight of 530, a weight average molecular weight of 820, and a molecular weight distribution of 1.56. PAPDMOS-a had a number average molecular weight of 780, a weight average molecular weight of 1490, and a molecular weight distribution of 1.90. Although polymerization had progressed in both samples, the molecular weights were observed to be low, at around pentamer to hexamer. The molecular weights were estimated to be lower than those obtained by MALDI-TOFMS measurement because the presence of amine groups made the samples more likely to be adsorbed onto the column, and it is thought that the calibration curve created with polyethylene glycol could not be properly calibrated. [Table 2]
[0052] A simple thermal curing test was conducted by heating and palpating the bulk sample. The viscosity of PAPDMOS-b decreased when heated. On the other hand, PAPDMOS-a, although a viscous liquid at room temperature, changed to a glass-like hardness after heating at 100°C for three hours. After hardening, PAPDMOS-a softened again to a viscous liquid when left under standard atmospheric pressure. It is believed that the naturally absorbed water was evaporated by heating, leading to the observed hardening behavior.
[0053] Figure 5 shows the results of evaluating the moisture absorption capacity of PAPDMOS-a and PAPDMOS-b using an electronic balance. As shown in Figure 5, the amount of moisture absorption increased with increasing humidity for both samples, and the amount of moisture absorption increased nonlinearly, especially at humidity levels of 70% or higher. The moisture absorption rate of sodium polyacrylate, a representative polymer with high moisture absorption capacity, is 88% (@90%RH)18, so it can be determined that PAPDMOS-a has superior moisture absorption capacity. Comparing the moisture absorption capacity of PAPDMOS-a and PAPDMOS-b, a difference in moisture absorption occurred at humidity levels of 60% RH or higher, with PAPDMOS-a absorbing more moisture. At 90% RH, the difference in moisture absorption capacity was nearly two times. The amount of moisture absorption is determined by the osmotic pressure of the polymer and its affinity with water19. The amine hydrochloride of PAPDMOS-a has a higher ion density and osmotic pressure than the amine of PAPDMOS-b. In addition, the amine hydrochloride has a higher affinity with water than the amine. For this reason, it is believed that PAPDMOS-a had better moisture absorption ability than PAPDMOS-b.
[0054] Next, the weight changes of the films obtained by QCM measurements of PAPDMOS-a and PAPDMOS-b are shown in Figures 6(a) and 6(b), respectively. PAPDMOS-a and PAPDMOS-b showed a rapid response of moisture absorption and desorption depending on the humidity. However, the relative moisture absorption amount at the highest humidity reached, 80% RH, was 40 wt%, which was lower than the moisture absorption amount obtained by the electronic balance. This is thought to be because the film liquefies in the high humidity region, which deteriorates the adhesion to the substrate, making it impossible to accurately measure the resonant frequency of the film.
[0055] (Evaluation of PAPDMOS-HCl) PAPDMOS-HCl 1In the H-NMR spectrum, the ratio of the peak of the proton derived from the quaternary amine to the proton of the carbon at around 1.6 ppm was both 2.0:3.0, so it was determined that almost 100% of the amine had become the hydrochloride salt. PAPDMOS-HCl was soluble in water, methanol, and DMSO, and showed the same solubility as PAPDMOS-a. Curing behavior by heating was also observed. It was revealed that even the polymer obtained by polycondensation under basic conditions (PAPDMOS-b) can be converted to the polymer obtained by polycondensation in the presence of hydrochloric acid (PAPDMOS-a) by mixing with hydrochloric acid.
[0056] (Evaluation of PAPDMOS-HBr) PAPDMOS-HBr 1In the H-NMR spectrum, the ratio of the peak of the proton derived from the quaternary amine to the proton of the carbon at around 1.6 ppm was both 2.0-3.0, so it was determined that almost 100% of the amine was converted to hydrobromide. PAPDMOS-HBr was soluble in water, methanol, and DMSO, and had the same solubility as PAPDMOS-a and PAPDMOS-HCl. It was found that PAPDMOS has the same solubility whether the counter anion of PAPDMOS is chlorine or bromine. In addition, curing behavior due to heat was observed. Figure 7 shows the results of evaluating the moisture absorption capacity of PAPDMOS-HBr using an electronic balance. For comparison, the data of PAPDMOS-a and PADMOS-b are also plotted. Like PAPDMOS-a, PAPDMOS-HBr was found to have excellent moisture absorption capacity. When comparing the moisture absorption amounts of PAPDMOS-HBr and PAPDMOS-b, no significant difference was observed at humidity levels below 80% RH, but PAPDMOS-HBr absorbed more moisture at humidity levels above 80% RH. This is because the osmotic pressure of the polymer and its affinity for water are higher for amine hydrobromides than for amines. When comparing the moisture absorption amounts of PAPDMOS-HBr and PAPDMOS-a, PAPDMOS-a had a greater moisture absorption amount. Between NaCl and NaBr, NaCl has a greater osmotic pressure (Japan Industrial Standards, Hygrometer - Test Method, JIS B7920), and it is believed that PAPDMOS-a showed superior moisture absorption capacity to PAPDMOS-HBr due to the hierarchy of osmotic pressures according to the counter anions of inorganic salts. It was found that moisture absorption capacity depends on the presence or absence and type of counter anion.
[0057] (Viscoelasticity measurement using a rheometer) The storage modulus of PAPDMOS-a, PAPDMOS-b, PAPDMOS-HCl, and PAPDMOS-HBr was measured at room temperature and humidity of 0% and 80%. The measuring instruments used were ARES-G2 (TA Instruments) and Discovery HR-2 (TA Instruments). The polymer sample was placed on a parallel plate with a diameter of 8 mm, and the cover of the sample chamber was closed. Nitrogen gas or dry gas was flowed into the sample chamber. After heating at 200°C for 30 minutes to thoroughly distill off the moisture absorbed from the sample, the cover of the chamber was opened to check the area around the sample, and the sample that had dripped from the plate was returned to the plate. Then, the plate above the sample was lowered and the sample was sandwiched between the parallel plates. The final sample gap was 0.5 mm to 1 mm.
[0058] The results of measuring the storage modulus of PAPDMOS-a, PAPDMOS-b, PAPDMOS-HCl, and PAPDMOS-HBr at room temperature and humidity of 0% and 80% are shown in Table 3 below. Comparing the modulus at 80% humidity (moisture absorption) with that at 0% humidity (dry), it was found that the modulus of PAPDMOS-a changed by approximately 100 million times. It was also found that the modulus of elasticity during curing changed depending on the type of counter ion. [Table 3]
[0059] (Adhesion test) An adhesion test was conducted on PAPDMOS-a to evaluate its adhesive strength. Figure 8 shows an outline of the preparation of the test piece for the adhesion test. The adhesive strength was evaluated by tensile shear. A slide glass S1111 (Matsunami) with a hole of 4 mm diameter at the edge was used as the substrate. A duct seal (3M) with a size of 1.5 mm square and a thickness of 0.19 mm was attached to the glass substrate that had been cleaned by ozone oxidation or wiping with acetone. This duct seal was previously treated by making a hole of 6 mm diameter in the center with a hole punch. A sample that had naturally absorbed moisture was placed in the depression in the center of the seal, and another glass substrate was placed over it so that the treated surface, the surface that had been ozone oxidized or wiped with acetone, was in contact with the sample. A weight of about 250 g was placed on the adhesive part, and the sample was hardened by heating at 100°C for 3 hours in a vacuum oven. After that, it was left to cool in a vacuum for 30 minutes and used as a test piece for evaluating adhesive strength. The adhesive strength of the cured sample was measured by inserting a hook fixed to the angle of the laboratory bench into a hole at one end of the test piece, and the hook of a digital force gauge DST500N (IMADA) into the hole at the other end, and pulling it in a direction parallel to the laboratory bench. The adhesive strength of the moisture-absorbed sample was measured by omitting the heating and drying process of the sample in a vacuum oven.
[0060] The adhesive strength of PAPDMOS-a measured with a digital force gauge is shown in Table 4 below. The force gauge value increased by about 20 to 30 times before and after the heat drying treatment. In addition, when the substrate was subjected to a hydrophilic treatment using ozone oxidation, the adhesive performance improved, and it showed a value of 50N or more, which is the limit value of the digital force gauge. The adhesive strength of the sample was calculated from the obtained force gauge value using the following formula.
number
[0061] The adhesive strength of PAPDMOS-a on the substrate wiped with acetone alone was 1.4 MPa, and on the substrate treated with ozone oxidation it was 1.8 MPa or more. 1M is Pa / 1cm 2This adhesive strength is enough to suspend a weight of approximately 10 kg per unit area. An adhesive strength of 1 MPa or more is sufficient for a removable adhesive material, in other words, for a temporary fixing. Furthermore, when PAPDMOS-a was exposed to high humidity (80% RH) overnight after bonding by heating and drying, the adhesive strength of the substrate decreased to the point where it peeled off under its own weight. These results demonstrate that the hardening phenomenon of PAPDMOS-a is useful as an adhesive material for temporary fixing.
[0062] The present disclosure has been described above based on the embodiments. These embodiments are merely examples, and it will be understood by those skilled in the art that various modifications are possible in the combination of each component and each treatment process, and that such modifications are also within the scope of the present disclosure. [Industrial Applicability]
[0063] The polysiloxanes of the present disclosure can be used as adhesives and humidity sensors. [Explanation of symbols]
[0064] 10 humidity sensor, 12 substrate, 14 humidity sensitive film.
Claims
1. A polysiloxane having a structure represented by the following formula (1): 【Chemistry 1】 wherein A is alkylene; B is an alkyl group; X is NH2+ and Y is a halide ion; R is hydrogen.
2. 2. The polysiloxane according to claim 1, which reversibly repeats hardening due to drying and softening due to moisture absorption.
3. Storage modulus at 0% humidity is 1.8 x 10 8 Pa ~ 8.1 x 10 8 Pa, and the storage modulus at 80% humidity is 6.2 x 10 0 Pa ~ 1.0 x 10 1 3. The polysiloxane according to claim 1, wherein the polysiloxane is a siloxane having a molecular weight of 1.0 or less.
4. 4. The polysiloxane according to claim 1, which has a tensile shear adhesive strength in a dry state to an ozone oxidation treated substrate of 0.8 MPa or more.
5. An adhesive comprising the polysiloxane according to any one of claims 1 to 4.
6. A humidity sensor comprising: a substrate; and a humidity-sensitive film formed on the substrate, the humidity-sensitive film comprising the polysiloxane according to claim 1 .
Citation Information
Patent Citations
Siliceous copolymer resistor type thin film humidity sensitive element and method for making same
CN1655375A
JP1964-017511B
Surface active polysiloxan*its manufacture and composition containing it
JP1980078020A
Curing composition
JP1996311347A
Reactive silyl group-containing ionic compound and siloxane skeleton-containing ionic compound
JP2018070545A